Designing Future Learning Environments : Lernumgebungen für die Entwicklung von Future Skills aus der Perspektive von Lehramtsstudierenden (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2024)
This article presents a qualitative study (N = 38) that investigates how student teachers perceive learning environments for the development of future skills. For this purpose, texts and drawings were analysed and discussed. The results show that the participating student teachers already have a perception of future skills and supportive learning environments. How interdisciplinary collaboration, creative use of digital tools or aspects of education for sustainable development can be integrated into skills-promoting learning environments should be further promoted in university teacher training programmes.
Keywords: Learning Environment; Futures Literacy; Space and Didactics; Education for Sustainable Development; Teacher Education